A terapia morfoanalítica como recurso terapêutico em mulheres pós-cirurgia de câncer de mama - Pachioni, Fernanda Stellutti Magrini [UNESP] (2014)
From the diagnosis of breast cancer, women experience severe physical and emotional repercussions. With the increasing number of cases of breast cancer, it is necessary to introduce more therapeutic resources in the recovery process of these women. The Morfoanalítica Therapy (TM), in psicocorporal performance, integrates the harmonization of muscular tensions, the adjustment of muscular chains compensation and development of the body and sensory exteroceptive and proprioceptive awareness, verbal working with the analytical, in all phases of the session . Therefore the aim of this thesis was to investigate the effect of TM on the quality of life, stress, flexibility, anxiety, depression and self-esteem , post- surgery for breast cancer women . Thus, the dissertation was divided into two items. In both studies involved 10 post- surgery breast cancer with a mean age of 53.2 ± 7.72 years women. In the first study, collections of personal and anthropometric data were performed. Then we were invited to answer the questionnaires on quality of life - SF -36 and the inventory of symptoms of stress (ISS) Lipp...